An effective strategy with tofacitinib for the management of focal myositis with rheumatoid arthritis: a case report - Jing Pan; Haihong Zheng; Juan Xu; Shaobiao Pan (Frontiers in Immunology, 2024)
Focal myositis is a rare, localized, benign, self-limiting, and non-suppurative inflammatory lesion of the skeletal muscle that may occasionally occur as a complication of rheumatic diseases. This case report discusses a 58-year-old patient with rheumatoid arthritis, who was diagnosed with focal myositis during standard immunosuppressive therapy. The patient was treated with tofacitinib; to our knowledge, this is the first reported case of focal myositis managed with this medication. Clinicians should maintain a suspicion for focal myositis in patients presenting with localized muscle swelling and pain, especially those with underlying rheumatic conditions. In cases where corticosteroid tapering proves difficult, tofacitinib may be considered as an alternative therapeutic strategy.